A6.12 Effects of anti-tnf therapy on markers of angiogenesis and vascular pathology in arthritis: a comparative approach. (13th February 2015) - Balogh, E; Végh, E; Kerekes, G; Váncsa, A; Csomor, P; Pogácsás, L; Balázs, F; McCormick, J; Biniecka, M; Szántó, S; Szűcs, G; Fearon, U; et al.
Abstract : Background and objectives: Accelerated atherosclerosis, increased cardiovascular (CV) morbidity and mortality, as well as the perpetuation of angiogenesis and abundant production of angiogenic factors have been associated with rheumatoid arthritis (RA) and ankylosing spondylitis (AS). Biologics may influence both vascular function and angiogenesis. However, the effects of targeted therapies on vascular function and angiogenesis have been poorly studied in a comparative manner. Therefore, vascular function, markers of atherosclerosis and angiogenesis, as well as the effects of anti-TNF therapy on these biomarkers were assessed in the very same arthritis patient cohort. Patients and methods: Altogether 31 arthritis patients including 18 RA patients treated with either etanercept (ETN) or certolizumab pegol (CZP) and 13 AS patients treated with ETN were included in a 12-month follow-up study. Ultrasonography was performed to determine flow-mediated vasodilation (FMD), a marker of endothelial dysfunction; common carotid intima-media thickness (ccIMT), a marker of atherosclerosis and pulse-wave velocity (PWV), an arterial stiffness parameter in all patients. Furthermore, circulating markers of angiogenesis including vascular endothelial growth factor (VEGF), platelet-derived growth factor-BB (PDGF-BB), angiopoetin 1 and 2(Ang1, Ang2) and thrombospondin 1 (TSP-1) were assessed in the sera by ELISA. DAS28, BASDAI and CRP, markers of disease activity, were also determined. All assessments were performed at baseline, as well as 6 and 12 months after treatment initiation. Results: Anti-TNF treatment was highly effective in both diseases, as the mean DAS28 decreased from 5.00 to 2.97 (p < 0.001) in RA, mean BASDAI decreased from 5.99 to 1.82 (p < 0.001) in AS and CRP decreased from 13.8 to 3.9 mg/l (p = 0.021) in RA+AS over a 12-month period. Anti-TNF treatment resulted in significant improvement in FMD (from 7.15% to 9.11%; p = 0.009) and a tendency of improvement in PWV (from 7.57 to 6.82 m/sec; p = 0.190). Among markers of angiogenesis, mean VEGF (from 268.3 to 222.6 pg/ml; p = 0.006) and PDGF-BB (from 8187 to 6020 pg/ml; p = 0.012) levels significantly decreased after 12 months of therapy. Moreover, PDGF levels after 12 months, as well as Ang2 levels at all time points correlated with disease duration (p < 0.05) and Ang1, Ang2 and TSP1 levels all correlated with CRP at baseline (p < 0.05). When markers of vascular function and angiogenesis were compared, baseline PDGF levels correlated with baseline ccIMT (p < 0.05). Conclusions: In a mixed cohort of RA and AS patients, anti-TNF therapy improved endothelial function and decreased the circulating levels of some angiogenic markers. Both impaired vascular function and the perpetuation of angiogenesis may be due to active systemic inflammation associated with these arthritides.